Konstruktivisime sebagai Pendekatan Alternatif dalam Hubungan Internasional - Iva Rachmawati, M.Si (Jurnal Paradigma, 2012)
In the study of international relation, Constructivism proposes an alternative way to analize international phenomenon. It evaluates that the two previous approach, Realism and Liberalism failed in explaining some policies makings by certain countries in differents issues. This approach is built above three elements, those are: relativism, subjectivism and the openness. Through these elements, constructivism tries to avoid the weakness as the positivist approach has, for instance: positivist believes that reality can only be explained by theoretical frame. Thus, the knowledge is based on deeds concepts or speech which has capability in building social constructivism.Furthermore, Constructivism tries to replace material condition to ideas as the base of international system. This is an important part of constructivism because ideas was put as the main factor on influencing state behaviours and international relations. The impact of this approach is we can find that instead of the defence and economic issues some issues, such as environmental issue, gender issue and human rights issue can determine state behaviours.